Wildfowl food research - Olney, P J S (Wildfowl, 1960)
That there is some sort of relationship between population size and density and the quality and quantity of food available and consumed is obvious, but the extent of this relationship is rarely known and then only when a detailed study of a particular species has been made. For most conservation work it is of fundamental importance to know how far food can be a limiting factor. Since 1957 the Wildfowl Trust has been carrying out a study of the food and feeding habits of various British wildfowl. This report is a summary of the work involved up to date.